2008
DOI: 10.1177/0149206308318619
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Investigation of Gender Differences in Mentoring

Abstract: This meta-analysis investigates gender differences in mentor-and protégé-reported experience in mentorships as well as career and psychosocial benefits. There are no gender differences in experience as a protégé or protégé receipt of career development, but male protégés report receiving less psychosocial support than female protégés. Furthermore, males are more likely to serve as mentors than females and report giving more career development than female mentors. Conversely, female mentors report providing mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 49 publications
7
134
2
2
Order By: Relevance
“…Our review revealed that none of the mentor or protégé demographic characteristics are meaningfully related to perceptions of instrumental support, psychosocial support, or relationship quality. This is generally consistent with previous meta-analytic research (Kammeyer-Mueller & Judge, 2008;O'Brien et al, 2010), although it should be noted that Kammeyer-Mueller and Judge (2008) found that in the workplace. White protégés reported slightly higher instrumental support (p = .11) than did nonWhites.…”
Section: Outputssupporting
confidence: 91%
See 1 more Smart Citation
“…Our review revealed that none of the mentor or protégé demographic characteristics are meaningfully related to perceptions of instrumental support, psychosocial support, or relationship quality. This is generally consistent with previous meta-analytic research (Kammeyer-Mueller & Judge, 2008;O'Brien et al, 2010), although it should be noted that Kammeyer-Mueller and Judge (2008) found that in the workplace. White protégés reported slightly higher instrumental support (p = .11) than did nonWhites.…”
Section: Outputssupporting
confidence: 91%
“…It may also reflect differences in gender-prescribed helping behaviors among mentors (Bogat & Liang, 2005) or differences in the power and resources that male and female mentors have to offer protégés (Ragins, 1997b). Existing research is mixed regarding whether the gender of the protégé and the gender of mentor relate to these three aspects of mentoring (e.g., H. M. Johnson, Xu, & Allen, 2007;Liang & Grossman, 2007;O'Brien et al, 2010;Ragins, 1999Ragins, , 2007.…”
Section: Demographicsmentioning
confidence: 99%
“…First, male mentors may simply pay more attention to career functions than female mentors. In line with the gender role congruency hypothesis, whereby male managers are expected to be agentic (e.g., instrumental and self-suffi cient) while women managers are expected to be communal (e.g., helpful and sympathetic) (Eagly and Karau 2002 ), a recent meta-analysis found that male mentors report giving more career development support to their mentees than female mentors while female mentors report giving more psychosocial support (O'Brien et al 2010 ). But only career functions impact women's advancement (Metz 2009 ;Tharenou 2005 ) and earnings (Johnson and Scandura 1994 ).…”
Section: Will You Mentor Me?mentioning
confidence: 97%
“…The pioneering work on mentoring [25], [26] suggested that mentoring is a powerful influence on success in organizational environments [27]. As a result of mentoring outputs, the protégé achieves a remarkable improvement in his professional career [28], [29], [30], a higher income [29], [31] and more satisfaction and social acceptance in the working environment [27], [32].…”
Section: A Review Of the Literature On Mentoringmentioning
confidence: 99%